TINGKAT RUJUKAN EMISI HUTAN MANGROVE DELTA MAHAKAM - Frida Sidik; Bambang Supriyanto; Mega Lugina (Centre for Research and Development on Social, Economy, Policy and Climate Change, 2017)
Forest Reference Emission Level (FREL) is one of four required elements for developing countries in implementing REDD+ activities, and serves as a benchmark in assessing REDD+ performance. This study assessed the emission level from mangrove deforestation in Mahakam Delta - East Kalimantan, aiming to enhance the baseline for subnational FREL document. Over the observation period of 1980-2001, conversion of mangrove forest into aquaculture ponds has resulted in a massive mangrove loss, with an estimation of 3,183 hectare/year, or equivalent to the release of 0.46 Tg CO2e/year. If soil pool was also included in the calculation, mangrove deforestation in Mahakam Delta between 1980 and 2001 emitted 2.9 TgCO2e/year. The CO2 emission from aquaculture ponds may couple with mangrove deforestation, which released 52 Gg CO2 /year from the pond floor. After 2001, the rate of mangrove deforestation decreased, allowing mangrove forests to recover with the expansion rate of 1,546 hectare/ year during 2001-2011 or equivalent to the carbon sequestration or removal of 0.67-4.7 TgCO2e/year. The results of the study suggest the way to improve the existing FREL by raising the importance of mangrove as “blue” carbon, with reference of the 2013 IPCC Guideline: Wetland Supplement.